NOD1/2 and the C-Type Lectin Receptors Dectin-1 and Mincle Synergistically Enhance Proinflammatory Reactions Both In Vitro and In Vivo - Tukhvatulin AI; Dzharullaeva AS; Erokhova AS; Scheblyakov DV; Naroditsky BS; Gintsburg AL; Logunov DY (Dove Medical Press, 2020)
Amir I Tukhvatulin, Alina S Dzharullaeva, Alina S Erokhova, Dmitry V Scheblyakov, Boris S Naroditsky, Alexander L Gintsburg, Denis Y Logunov N. F. Gamaleya National Research Center for Epidemiology and Microbiology, Moscow, RussiaCorrespondence: Amir I Tukhvatulin Gamaleya Str.18, Moscow 123098, RussiaTel/ Fax +74991904373Email amir_tukhvatulin@gamaleya.orgPurpose: Pathogens consist of a wide variety of evolutionarily conserved molecular structures that are recognized by pattern recognition receptors (PRRs) of innate immunity. Reasonably assuming that no single PRR is ever likely to be the sole trigger of the immune response during infection, a great deal remains unknown about collaborative mechanisms and consequential crosstalk effects between multiple PRRs belonging to different families. Here, we aimed to investigate inflammatory response to combined stimulation of cytosolic nucleotide-binding oligomerization domain (NOD) receptors: NOD1, NOD2 and membrane-bound C-type lectin receptors (CLRs): Mincle and Dectin-1 in comparison to individual stimulation both in vitro and in vivo.Materials and Methods: For in vitro studies, we used human monocytic THP-1 cells endogenously expressing NOD1,2, as well as Mincle and Dectin-1 receptors. Using reporter gene and immunoassay approaches, we measured activity of key proinflammatory transcription factors (NF-κB and AP-1) and cytokine production after addition of specific PRR agonists or their pairwise combinations. In vivo NF-κB activity (bioluminescent detection in NF-κB-Luc transgenic mice), as well as cytokine levels in mouse blood serum, was measured 3 hours after intramuscular injection of PRR agonists.Results: We detected that combined stimulation of NOD1/2 and C-type lectin receptors (Dectin-1, Mincle) strongly potentiates NF-κB and AP-1 transcription factor activity in human monocytic THP-1 cells, as well as resulting in enhanced levels of IL-8 cytokine production. We demonstrated that RIP2- and Syk-dependent signaling pathways downstream of NOD1/2 and Dectin-1/Mincle, respectively, are essential for the potentiated proinflammatory cell response. Lastly, we confirmed that synergy between NOD and C-type lectin receptors resulting in potentiated levels of NF-κB activation and cytokine (IL-6, KC) production also occurs in vivo.Conclusion: These findings originally indicate cooperation between NODs and CLRs, leading to potentiated levels of proinflammatory immune response both in vitro and in vivo.Keywords: pattern recognition receptors, innate immunity, synergy, collaboration